Sosialisasi Program Bantuan Hukum Nonlitigasi di Desa Wanayasa Kabupaten Cirebon - Rahmat, Diding; Junaedi, Junaedi (Empowerment : Jurnal Pengabdian Masyarakat, 2022)
The legal aid program policy is a program that aims to provide access to justice for everyone, including the poor. In its implementation, as in the Law on Legal Aid, there are litigation legal aid programs and non-litigation legal aid programs. The litigation legal aid program is in the form of handling cases related to law enforcement institutions or apparatus in a predetermined judicial system, while the non-litigation legal aid program is a legal aid program that is not in conflict with the existing justice system. In this outreach socialization event, the legal basis of the non-litigation legal aid program was conveyed and what forms the program took. The approach method for implementing the activities used in this Community Service is through a workshop approach method, lectures then at the end of the event a question-and-answer session is held, with this question and answer the community is given the opportunity to ask questions according to the counseling theme, or the public can ask questions outside the predetermined theme. The benefit of holding legal counseling in Wanayasa Village, Cirebon Regency, West Java Province is that the community knows the rules regarding non-litigation legal aid programs and what forms of non-litigation legal aid.